Acerca de la antigua importancia de las comparsas de wayri chu’nchu y su contemporánea marginalidad en la peregrinación de Quyllurit’i - Salas Carreño, Guillermo (2010)
This paper proposes some ideas regarding the history of the Quyllurit’i pilgrimage by paying close attention to the particularities of the wayri ch’unchu ritual dance. After reviewing the available historic evidence about it, the text proposes that the location of the shrine at the bottom of the Qulqipunku glacier (Ocongate, Cusco) is explained by its liminal position between the Andean highlands and the Amazon. The location of the Qulqipunku, and its difference with the Ausangate, is very evident for the communities living in the surroundings of Qulqipunku. The text proposes that these communities were the main protagonists of the pilgrimage at least until the end of the 19th century. The paper explains why the wayri ch’unchudancers of these communities —highlanders who represent indigenous peoples of the Amazon— were so important and numerous in the past. Finally, the text shows how the continuous grow of the pilgrimage along the 20th century has meant a progressive marginalization of these communities within the pilgrimage as well as a clear decrease in the preponderance of wayri ch’unchu dancers. The decrease is directly related to attempts to subvert ideologies of social differentiation present in the region that are framed in a broader and ongoing process of de-indianization.